Roll-to-roll manufacturing of flexible acetone sensors - Ya-Ching Yu; Nicholas Glassmaker; Ana M. Ulloa; Benson Kunhung Tsai; Amit Barui; Haiyan Wang; Lia Stanciu (PLoS ONE, 2025)
A fully roll-to-roll (R2R) manufactured conductometric sensor has been developed for acetone detection. It features flexible, screen-printed silver electrodes modified with a MoS2 and single-walled carbon nanotube (SWCNT) nanocomposite. The electro-spraying process allowed for the simultaneous fabrication of over 100 electrodes. The optimized electro-sprayed electrodes showed a consistent average resistance of 99.63 Ω (SD = 8.10), ensuring uniform and reliable sensor performance for volatile organic compounds (VOCs) detection. SEM and TEM analyses revealed that the porous 3D MoS 2 -SWCNT network enhances gas adsorption and sensor performance. To improve acetone selectivity, electrodes were functionalized with tetrafluorohydroquinone (TFQ), which binds with acetone and facilitates charge transfer, reducing holes in p-type SWCNT and increasing resistance. Sensitivity was further optimized by adjusting film deposition parameters, with a thinner MoS 2 layer (~30 nm) improving the response to 20% acetone by 120%. Stability tests confirmed 90% signal retention after 30 days in nitrogen. This study proposed the first platform of a MoS 2 -SWCNT nanocomposite in R2R manufacturing for flexible acetone sensors. The approach provides a scalable solution, bridging lab-scale research with industrial production and advancing practical VOC detection applications.